Identification of the NRF2 transcriptional network as a therapeutic target for trigeminal neuropathic pain - Vasavda, Chirag; Xu, Risheng; Liew, Jason; Kothari, Ruchita; Dhindsa, Ryan S.; Semenza, Evan R.; Paul, Bindu D.; Green, Dustin P.; Sabbagh, Mark F.; Shin, Joseph Y.; Yang, Wuyang; Snowman, Adele M.; et al. (Science advances, 2022)
Trigeminal neuralgia, historically dubbed the “suicide disease,” is an exceedingly painful neurologic condition characterized by sudden episodes of intense facial pain. Unfortunately, the only U.S. Food and Drug Administration (FDA)–approved medication for trigeminal neuralgia carries substantial side effects, with many patients requiring surgery. Here, we identify the NRF2 transcriptional network as a potential therapeutic target. We report that cerebrospinal fluid from patients with trigeminal neuralgia accumulates reactive oxygen species, several of which directly activate the pain-transducing channel TRPA1. Similar to our patient cohort, a mouse model of trigeminal neuropathic pain also exhibits notable oxidative stress. We discover that stimulating the NRF2 antioxidant transcriptional network is as analgesic as inhibiting TRPA1, in part by reversing the underlying oxidative stress. Using a transcriptome-guided drug discovery strategy, we identify two NRF2 network modulators as potential treatments. One of these candidates, exemestane, is already FDA-approved and may thus be a promising alternative treatment for trigeminal neuropathic pain. Pharmacologically and genetically recruiting the NRF2 transcriptional network alleviates trigeminal neuropathic pain.